Estudantes moçambicanos em Belo Horizonte: uma discussão sobre a construção identitária e de redes de sociabilidade - Ngomane, Yara Neusa (2010)
The paper shows how identity processes are built for Mozambican students established in Belo Horizonte - arriving through agreements between governments and higher institutions of both countries - and how are woven their social networks. To this end, these students were observed as they related to each other, with Brazilians and Africans of other nationalities in their daily life. Through the fieldwork was noted in this migration, family networks and kinship being re-built. Likewise, through stories of prejudice and exoticism about the way of being and living of these individuals, their phenotype and behavior, it was perceived as ethnic and race relations were taking place and these students were transformed into Brazilian territory. Thus, throughout the dissertation refers to the concepts of ethnicity, race, nationality, kinship and social networks because they are interwoven to show a better understanding of the presence of Mozambican students in Brazil.